COMT methylation as a potential peripheral biomarker of schizophrenia - Abd. Rahim, Nour El Huda; Rahim Mohd, Nabil Fikri; Mohd Noor, Hanisah; Abdullah, Kartini; Ku Zaifah, Norsidah; A. Talib, Norlelawati (2017)
Schizophrenia is a common debilitating neuropsychiatry disorder. Currently, absolute clinical criteria (DSM-V) are used for the diagnosis. Identification of prediction and therapeutic markers of schizophrenia could expedite the disease diagnosis and management. Catechol-O-methyltransferase (COMT) which regulates catecholamine and cognitive function in the developing neurons has long been considered as one of the candidate genes of schizophrenia. Recent studies have discovered hypomethylation of the COMT gene in the brain of schizophrenia patients. Our study aims to assess the COMT DNA methylation in the peripheral blood, on the premises that there are global epigenetic changes and the changes in the peripheral blood mirrors the methylation changes of the brain in the schizophrenia patients and the healthy controls. 138 schizophrenia patients from the Psychiatry Clinic, Hospital Kuantan Ampuan Afzan, Kuantan Pahang and 132 matched healthy controls from Kuantan district were recruited. Genomic DNA from the peripheral blood was bisulfite converted and quantitatively measured for the COMT DNA methylation using the MethyLight Taqman® assay and normalized with the ALU reference control to give the percentage methylation ratio. We found a significant hypomethylation of COMT in schizophrenia as compared to the control group (p=0.000). The hypomethylation was also significant in males (p=0.002) and females (p=0.032). This study suggests that DNA methylation analysis of COMT can be a potential peripheral biomarker in schizophrenia.